2009
DOI: 10.1007/s10620-009-0963-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Trends in the Incidence of Inflammatory Bowel Disease in Korean Children: A Single-Center Experience

Abstract: Background Inflammatory bowel disease (IBD) is rare in Asian children and few reports on pediatric IBD have appeared. Aims We, therefore, investigated the incidence trends and clinical characteristics of pediatric IBD in Korea. Methods We enrolled 48 children with Crohn's disease (CD) and 14 children with ulcerative colitis (UC) from 1996 to 2007. Trends in annual enrollment and clinical characteristics were retrospectively evaluated by medical record review. Results During the 12 years of observation, the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
57
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 36 publications
(72 reference statements)
14
57
3
Order By: Relevance
“…The extra-intestinal manifestations were less in our patients than in American children, but similar to those in Korean childen. [5,9] IBD was associated with other diseases in 13.3% of our patients. The association of FMF with IBD was reported previously.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The extra-intestinal manifestations were less in our patients than in American children, but similar to those in Korean childen. [5,9] IBD was associated with other diseases in 13.3% of our patients. The association of FMF with IBD was reported previously.…”
Section: Discussionmentioning
confidence: 68%
“…[4,5,[7][8][9][10] Most studies [4,5,[7][8][9][10] revealed that the incidence of IBD is increasing in childhood and the increment is more prominent in CD. The studies also found obesity related IBD, secondary IBD due to immune deficiencies or autoimmune diseases, and a high rate of colectomy in patients with UC.…”
Section: Introductionmentioning
confidence: 99%
“…Although about 25% of Crohn patients are diagnosed as children and adolescents, and their clinical features differ from those of adults [7], only a few Korean studies involving a small number of patients have been published to date [8910]. Data on the differences between the EIMs of IBD in children and adults are also lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, the latest studies have reported a gradually increasing incidence of CD in Asian populations 1,2. The incidence of CD in Korean adults has been increasing,3 and it has been suggested that the incidence in children is also increasing 4…”
Section: Introductionmentioning
confidence: 99%